Estimation of serum creatinine, serum urea, glomerular filtration rate and proteinuria among apparently healthy adults to assess the renal impairment and its association with body mass index: An observational hospital-based study - Singh Ray, Amit; Kumar Kare, Pawan; Makwane, Haresingh; Saxena, Tripti; Garg, Chitransh (International Journal of Medical Research and Review, 2020)
Background: Serum urea, creatinine, and estimated glomerular filtration rate (eGFR) are the most widely accepted parameters for the assessment of renal impairment. Renal dysfunction in Indian obese adults has not been sufficiently investigated. Aims: To evaluate the renal function by using serum urea, serum creatinine, eGFR, and proteinuria in normal, overweight, and obese adults to identify renal impairment. Materials and Methods: This observational and cross-sectional study was done on a total of 100 normoglycemic, normotensive healthy adults, and these were divided into three groups as per the criteria of body mass index (BMI) as; normal, overweight and obese groups. Estimation of urea and creatinine was done by fully automated chemistry analyzer methods. eGFR was calculated by Modified Diet Renal Disease (MDRD) formula. The excretion of protein in urine was checked by the urine dipsticks method. p<0.05 was considered as significant level. Results: The present study was conducted in 100 normal study subjects which included 48 males and 52 females. A maximum number of subjects were found in the obese subgroup (34%). Among subjects low eGFR prevalence was found 3% and prevalence of chronic kidney disease (CKD) was also found 3%. The obese subjects showed higher urea and creatinine levels compared to normal subjects. A significant negative relationship was noted in eGFR (MDRD) and BMI. The prevalence of proteinuria among subjects was 3%. Conclusions: A total of 3% prevalence of renal dysfunction was noted among adults and out of this 2% was found in obese adults. Therefore, it can be concluded that increasing BMI has a significant contributing factor for renal impairment in obese adults.